High-molecular-weight carbon dioxide-based elastomer, cross-linked carbon dioxide-based elastomer and preparation method of cross-linked carbon dioxide-based elastomer
Through the combination of homogeneous catalysts and heterogeneous catalysts, the carbon dioxide-based polymerization reaction is synergistically catalyzed, and the problems of low catalytic activity and unstable reaction in the prior art are solved, and high molecular weight and high performance carbon dioxide-based elastomers are prepared.
Patent Information
- Application Number
- CN202510276210.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-03-10
AI Technical Summary
In the preparation of high-molecular-weight carbon dioxide-based elastomers, the catalytic activity and unstable reaction process are produced, resulting in low molecular weight and poor mechanical properties of the product, making it difficult to meet the application needs of high-performance elastomers.
By combining homogeneous catalysts and heterogeneous catalysts, the synergistic catalytic effect is used to improve the catalytic activity and stability of the polymerization reaction, and a high molecular weight carbon dioxide-based elastomer is prepared.
The overall efficiency and stability of the catalytic system are significantly improved, and the obtained carbon dioxide-based elastomer has high molecular weight and excellent mechanical properties, which is suitable for a variety of application fields.
Smart Images

Figure CN119955078A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high molecular weight carbon dioxide-based elastomer, a cross-linked carbon dioxide-based elastomer and a preparation method thereof. Background Art
[0002] Using carbon dioxide (CO2) as a raw material to prepare polymer materials has become one of the important research directions of the chemical industry, with the characteristics and advantages of carbon fixation and turning waste into treasure. However, the current CO2-based copolymers are mostly focused on the development of rigid materials, such as polycarbonate (PPC) and polycyclohexene carbonate (PCHO), while there are fewer studies in the field of elastomeric materials. Compared with rigid materials, elastomeric materials are widely needed in the fields of automobiles, construction, medical treatment, electronics, etc. due to their unique deformation recovery ability, excellent fatigue resistance and processability. Therefore, the development of high-performance CO2-based elastomers is of great significance to broaden the application scope of carbon dioxide resource utilization.
[0003] CO2-based plastics usually have a higher glass transition temperature (Tg), show strong rigidity and mechanical strength at room temperature, and are suitable for fields such as engineering plastics and packaging materials. Usually, CO2-based plastics need to find ways to increase their Tg to ensure their performance; while CO2-based elastomers need to maintain a lower Tg (usually below 0°C) at room temperature to provide excellent elasticity and flexibility.
[0004] In order to lower Tg and keep the material elastic at room temperature, it is usually necessary to introduce epoxy monomers with long side groups into the polymer main chain. However, the molecular structure of this type of monomer is large and the steric hindrance is high. The commonly used catalysts often show low activity when facing long side group monomers, resulting in a decrease in the polymerization reaction rate and difficulty in generating high molecular weight polymers [J.Polym.Sci.PartA:Polym.Chem.,2015,53,737;Macromol.Symp.2005,224,181.;ACSMacro Lett.2022,11,945]. Molecular weight is one of the key parameters that determine the properties of polymers. Generally speaking, high molecular weight CO2-based polymers usually have better mechanical properties, thermal stability and processability. In elastomer applications, an increase in molecular weight can effectively improve the tensile strength, toughness and resilience of the material, enhance its service life, and expand its application range. However, it is often difficult to obtain high molecular weight polymers when synthesizing CO2-based elastomers using existing catalytic systems. This is mainly attributed to the insufficient activity, poor selectivity and high proportion of side reactions of the catalyst, which directly affect the efficiency of the polymerization reaction and the molecular weight and distribution of the final product. Therefore, the development of a new catalytic system that can efficiently control the polymerization process and increase the molecular weight of the target product is crucial for the research of CO2-based elastomers.
[0005] For the catalyst system of CO2-based polymer synthesis, the current catalytic systems are mainly divided into two categories: homogeneous catalysts and heterogeneous catalysts. Bimetallic catalysts are heterogeneous catalytic systems that have been studied more and applied in industry. This type of catalyst has high catalytic activity and can effectively promote the copolymerization of epoxy monomers and CO2. However, there are still many problems with bimetallic catalysts in practical applications. For example, their reaction induction period is long, and it takes a long time to achieve efficient catalysis; in addition, during the catalytic process, it is often accompanied by a high proportion of ether segments (about 40%) (SusMat.2021; 1:91), resulting in poor selectivity of polycarbonate, low molecular weight of the final product, and wide molecular weight distribution (patent CN 114479045A), which is difficult to meet the application requirements of high-performance elastomers.
[0006] Aluminum porphyrin and Salen Co catalysts are currently typical homogeneous catalytic systems. Salen Co catalyst shows extremely high catalytic activity in the copolymerization of cyclopropane and CO2. However, when faced with epoxides containing long side groups, its selectivity decreases significantly, resulting in a significant decrease in the polymerization reaction rate (patent CN1560111A). Aluminum porphyrin catalysts show high selectivity in the copolymerization of CO2 and long side group epoxides. The resulting polymer contains no ether segments, is 100% polycarbonate structure, and has a narrow molecular weight distribution. However, due to the limitations of its catalytic mechanism, a high proportion of cyclic by-products are easily generated during the reaction, and it is ultimately difficult to obtain high molecular weight polymers (Macromol.Chem.Phys.2022,223,2100403).
[0007] The existing technology has the following deficiencies in the preparation of carbon dioxide-based elastomers: (1) The catalytic activity of homogeneous catalysts is low, resulting in a slow polymerization reaction rate, which limits the polymerization efficiency; in addition, they have poor selectivity for long side-group epoxy monomers, are prone to side reactions, and are difficult to obtain high molecular weight polymers. (2) Although heterogeneous catalysts have high catalytic activity, their reaction induction period is long, and once the reaction is initiated, the rate may be too fast or even out of control, affecting the stability of the reaction, and ultimately resulting in a decrease in the mechanical properties and processing properties of the resulting polymer.
[0008] Therefore, how to effectively combine the advantages of homogeneous catalysts and heterogeneous catalysts to develop an efficient and stable catalytic system to achieve the preparation of carbon dioxide-based elastomers with high molecular weight, low Tg and excellent mechanical properties has become a key technical problem that needs to be solved urgently. Summary of the invention
[0009] The present invention aims at the above problems in the prior art and proposes a catalyst system and a preparation method for preparing a high molecular weight carbon dioxide-based elastomer, which is particularly suitable for the field of elastomer materials. By compounding a homogeneous catalyst and a heterogeneous catalyst and utilizing their synergistic catalytic effect, the catalytic activity of the polymerization reaction, the carbonate unit content and the molecular weight of the polymer are significantly improved.
[0010] One of the purposes of the present invention is to provide a high molecular weight carbon dioxide based elastomer obtained by polymerization reaction of components including carbon dioxide and epoxy compounds under the action of a composite catalyst, wherein the composite catalyst comprises a homogeneous catalyst, a heterogeneous catalyst and a co-catalyst.
[0011] According to the present invention, in the high molecular weight carbon dioxide based elastomer:
[0012] The epoxy compound comprises a saturated epoxy compound and an unsaturated epoxy compound; preferably, the saturated epoxy compound is selected from at least one of C3-12 saturated alkyl epoxy compounds, and the unsaturated epoxy compound is selected from at least one of unsaturated glycidyl ether compounds; more preferably, the saturated epoxy compound is selected from at least one of butylene oxide, hexylene oxide, and octane oxide; the unsaturated epoxy compound is selected from at least one of allyl glycidyl ether and glycidyl methacrylate; the molar ratio of the saturated epoxy compound to the unsaturated epoxy compound is 1:(0.01-0.5), preferably 1:(0.05-0.3);
[0013] The homogeneous catalyst is aluminum porphyrin;
[0014] The heterogeneous catalyst is selected from a bimetallic catalyst, preferably a Zn-Co bimetallic cyanide;
[0015] The co-catalyst is bis-(triphenylphosphorane)ammonium chloride (PPNCl);
[0016] The mass ratio of the homogeneous catalyst, the heterogeneous catalyst and the co-catalyst is 1:(0.05-0.7):(0.2-1.5), preferably 1:(0.1-0.5):(0.3-0.9).
[0017] The second object of the present invention is to provide a method for preparing the above-mentioned high molecular weight carbon dioxide-based elastomer, comprising heating and polymerizing the components including the carbon dioxide, epoxy compound, and composite catalyst, and then performing post-treatment to obtain the high molecular weight carbon dioxide-based elastomer.
[0018] According to an embodiment of the present invention, in the method for preparing the high molecular weight carbon dioxide-based elastomer:
[0019] In the composite catalyst, the amount of the heterogeneous catalyst is 0.002-0.12wt% of the total amount of the epoxy compound, preferably 0.008-0.1wt%; the amount of the homogeneous catalyst is 0.005-0.35wt% of the total amount of the epoxy compound, preferably 0.01-0.28wt%; the amount of the co-catalyst is 0.005-0.25wt% of the total amount of the epoxy compound, preferably 0.01-0.20wt%;
[0020] The polymerization reaction temperature is 50-80°C, preferably 55-70°C;
[0021] The polymerization reaction pressure is 2-6 MPa, preferably 3-5 MPa;
[0022] The polymerization reaction time is 1 to 24 hours, preferably 4 to 16 hours;
[0023] The post-treatment comprises the steps of dissolving, precipitating and drying; preferably, the dissolving solvent used in the dissolving is selected from at least one polar solvent, preferably at least one of dichloromethane and tetrahydrofuran; the precipitation solvent used in the precipitation is selected from at least one alcohol, preferably at least one of methanol and ethanol; the drying temperature is 25-60°C, preferably 30-40°C.
[0024] The present invention overcomes the technical difficulties of low catalytic activity, unstable reaction process and low product molecular weight in the prior art through the synergistic effect of homogeneous catalyst and heterogeneous catalyst, which is specifically manifested as follows:
[0025] (1) Synergistic effect of homogeneous catalysts and heterogeneous catalysts
[0026] The present invention significantly improves the overall efficiency and stability of the catalytic system by rationally compounding homogeneous catalysts (such as aluminum porphyrin) and heterogeneous catalysts (such as Zn-Co double metal cyanide), utilizing the ability of homogeneous catalysts to efficiently initiate reactions, and the stable catalytic effect of heterogeneous catalysts in the subsequent reaction stage. Among them, the homogeneous catalyst is responsible for quickly starting the polymerization reaction of epoxides and carbon dioxide, while achieving high selectivity and structural controllability of the initial product through its good molecular design; the heterogeneous catalyst plays a role in the middle and late stages of the reaction, stably promoting the chain growth reaction, ensuring the improvement of the molecular weight of the polymer, and combining the homogeneous catalyst with the heterogeneous catalyst for the preparation of carbon dioxide-based elastomers, achieving the synergistic effect of the catalytic system.
[0027] (2) Controllable reaction system
[0028] By adjusting the ratio of homogeneous catalysts to heterogeneous catalysts, catalyst loading, the type and ratio of epoxy monomers, and reaction conditions (such as temperature, pressure, and reaction time), the present invention can effectively control the microstructure, molecular weight, and distribution of the product, and prepare a carbon dioxide-based elastomer with a high molecular weight and excellent mechanical properties.
[0029] The third object of the present invention is to provide a high molecular weight carbon dioxide-based elastomer obtained by the above preparation method. Preferably, the number average molecular weight of the high molecular weight carbon dioxide-based elastomer is 50 to 180 kg / mol, preferably 80 to 150 kg / mol.
[0030] A fourth object of the present invention is to provide a cross-linked carbon dioxide-based elastomer prepared from a high molecular weight carbon dioxide-based elastomer, wherein the high molecular weight carbon dioxide-based elastomer is the above-mentioned high molecular weight carbon dioxide-based elastomer.
[0031] The fifth object of the present invention is to provide a method for preparing the above-mentioned cross-linked carbon dioxide-based elastomer, comprising the step of preparing the cross-linked carbon dioxide-based elastomer by subjecting the high molecular weight carbon dioxide-based elastomer to an initiation reaction; specifically comprising the following steps: mixing the high molecular weight carbon dioxide-based elastomer and an initiator and subjecting the mixture to a heating cross-linking reaction to obtain the cross-linked carbon dioxide-based elastomer; wherein the mixing is optionally carried out in a solvent.
[0032] According to an embodiment of the present invention, in the method for preparing the cross-linked carbon dioxide-based elastomer:
[0033] The initiator is selected from at least one of peroxide initiators, preferably at least one of dicumyl peroxide, di-tert-butyl peroxide, and 2,5-dimethyl-2,5-di-tert-butylhexane peroxide;
[0034] The solvent is selected from at least one of tetrahydrofuran, dichloromethane and toluene. The amount of the solvent is not particularly limited and can be adjusted within a wide range according to the commonly used amount;
[0035] The amount of the initiator is 0.03-0.20wt% of the amount of the high molecular weight carbon dioxide based elastomer, preferably 0.05-0.15wt%;
[0036] The temperature of the cross-linking reaction is 120-210°C, preferably 150-180°C;
[0037] The pressure of the cross-linking reaction is 10-20 MPa, preferably 13-17 MPa.
[0038] The present invention adopts a composite catalytic system combining a homogeneous catalyst and a heterogeneous catalyst for the efficient preparation of a high molecular weight carbon dioxide-based elastomer. Through the synergistic effect of the homogeneous catalyst and the heterogeneous catalyst, the present invention has the following beneficial effects:
[0039] (1) The technical solution of the present invention significantly improves the activity and reaction efficiency of the catalytic system through the efficient initiation of the homogeneous catalyst and the stable promotion of the heterogeneous catalyst. Compared with the traditional heterogeneous catalytic process, the reaction induction period is shortened to 50%, and at the same monomer conversion rate, the reaction time is shortened to 50% to 80% of the homogeneous catalytic process.
[0040] (2) The technical solution of the present invention optimizes the stability of the reaction process and suppresses the excessive catalytic speed of the heterogeneous catalyst, thereby effectively avoiding the problem of reduced polycarbonate content due to runaway reaction.
[0041] (3) The composite catalytic system of the present invention effectively avoids the problem of molecular weight limitation when homogeneous catalysts and heterogeneous catalysts are used alone. The number average molecular weight M of the prepared carbon dioxide-based elastomer is n It can reach 50~180kg / mol.
[0042] (4) The catalytic system of the present invention is applicable to the polymerization reaction of various epoxides (such as octane oxide, butylene oxide, allyl glycidyl ether) and carbon dioxide, has strong versatility, and lays a foundation for the further development of multifunctional carbon dioxide-based polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The curves of the conversion rate of 1,2-epoxyhexane monomers versus reaction time in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 1 It can be seen that the polymerization induction period in Example 1 is 1 h, and the 1,2-epoxyhexane monomer conversion rate reaches 80% after 6 h of reaction; the reaction in Comparative Example 1 has almost no induction period, and the 1,2-epoxyhexane monomer conversion rate is only 30%; the reaction induction period of Comparative Example 2 is >2 h.
[0044] Figure 2 The GPC curves of the carbon dioxide-based elastomers obtained in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 2 It can be seen that the GPC curve of the product in Comparative Example 1 is a bimodal distribution, the peak corresponds to a long retention time (low molecular weight), and the distribution is narrow, indicating that the product molecular weight is low and the distribution is narrow; the GPC curve of the product in Comparative Example 2 is a unimodal distribution, the peak corresponds to a long retention time (low molecular weight), and the distribution is wide; the GPC curve of the product in Example 1 is widely distributed, and the peak of the main product corresponds to a short retention time, indicating that the product molecular weight is high.
[0045] Figure 3The GPC curves of the carbon dioxide-based elastomer obtained at different times during the polymerization process of Example 1. In the initial stage of the reaction (<1.5h), the reaction rate is slow, and the GPC curve is bimodal, indicating that the copolymerization is initiated by aluminum porphyrin. As the reaction time is extended (>1.5h), the reaction rate increases due to the co-participation of Zn-Co double metal cyanide and aluminum porphyrin in the chain growth reaction, and the GPC curve is trimodal. This shows that the synergistic principle of the homogeneous catalyst quickly initiating the reaction and the heterogeneous catalyst stably promoting the polymerization.
[0046] Figure 4 The mechanical property curves of the cross-linked carbon dioxide-based elastomers obtained in Example 1 and Comparative Examples 1-2 are shown. Figure 4 It shows that the cross-linked carbon dioxide-based elastomer prepared by the composite catalytic system in Example 1 exhibits higher stress and strain. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0048] The test instruments and test conditions used in the examples are as follows:
[0049] Monomer conversion rate: Bruker AV600 NMR spectrometer ( 1 H NMR) was performed with deuterated chloroform (CDCl3) as solvent and tetramethylsilane (TMS) as internal standard. 1 The changes in the characteristic peaks of the monomers were analyzed by H NMR integration, and the conversion rate was calculated.
[0050] Molecular weight: Gel permeation chromatography (GPC) was used to determine the number average molecular weight (Mn) and molecular weight distribution index (PDI). A Waters 515 GPC instrument was used, equipped with Waters Styragel HT3, HT5 and HT6 series columns, with tetrahydrofuran (THF) as the mobile phase and a flow rate of 1.0 mL / min. Monodisperse polystyrene standards were used for calibration, and the molecular weight range covered 1620 to 8500 kDa.
[0051] Tensile test: Tensile strength and elongation at break were measured using a computer-controlled electronic universal testing machine (Zwick / Roell, Txet-port II, Germany) at a test speed of 50 mm / min and a test temperature of 25°C. The specimen size was prepared according to ISO 37:2005, with a narrow parallel section length of 20 mm and a width of 4 mm. Each sample was tested 3 times, and the mechanical properties were evaluated based on the test results.
[0052] Thermal properties analysis: Differential scanning calorimetry (DSC) was performed using a Mettler Toledo DSC instrument under nitrogen atmosphere to determine the glass transition temperature (T) of the polymer. g The sample was first heated to 100°C at a heating rate of 10°C / min and kept at this temperature for 5 minutes; then cooled to -100°C at a cooling rate of 10°C / min and heated again to 100°C at the same heating rate.
[0053] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0054] Preparation method of aluminum porphyrin catalyst:
[0055] Under argon protection, 0.7 mL of distilled pyrrole and 1.41 g of p-chlorobenzaldehyde were added to 400 mL of distilled dichloromethane, followed by the addition of 0.7 mL of trifluoroacetic acid. After stirring at 25°C for 1 h, 4.54 g of dichlorodicyanobenzoquinone (DDQ) was added, followed by further stirring for 1 h and filtration. The filtrate was distilled under reduced pressure to remove dichloromethane to obtain a purple-black solid, which was separated by a chromatographic column (stationary phase: neutral aluminum oxide; mobile phase: V (dichloromethane): V (petroleum ether) = 1:1) to obtain the ligand. Under argon protection, 20 mL of dichloromethane was added to a 50 mL round-bottom three-necked flask containing 0.753 g of the ligand, and the mixture was stirred at 25° C. until the ligand was completely dissolved. Subsequently, 1.3 mL of diethylaluminum chloride in n-hexane (1 mol / L) was added, and the mixture was stirred at 25° C. for 1 h, and the solvent was dried using a rotary evaporator. The crude product was separated by a chromatographic column (stationary phase: neutral alumina trioxide; mobile phase: V (dichloromethane): V (methanol) = 10:1) to obtain the catalyst used for polymerization.
[0056] Preparation method of zinc-cobalt double metal cyanide:
[0057] 1.33 g of K3Co(CN)6 was dissolved in 20 mL of deionized water to form a K3Co(CN)6 aqueous solution, and 3.26 g of ZnCl2 was dissolved in 60 mL of deionized water and 30 mL of tBuOH to form a mixed solution of ZnCl2. The ZnCl2 mixed solution was stirred at 50°C with a mechanical stirring speed of 300 rpm, and at the same time, 20 mL of K3Co(CN)6 aqueous solution was added dropwise to the ZnCl2 mixed solution through a constant pressure dropping funnel within 1 hour. After the addition was completed, stirring was continued under this condition for 1 hour, and then the filter cake was separated by centrifugation at a centrifugal speed of 5000 rpm for 5 minutes. The filter cake was then washed and pulped with a mixed solution of 30 mL of tBuOH and 30 mL of deionized water at 50°C and 300 rpm for 30 minutes, and then centrifuged at 5000 rpm for 5 minutes to separate the filter cake. The above washing, pulping and centrifugal separation process was repeated, and the amount of tBuOH and deionized water was gradually changed to 36 mL and 24 mL, 42 mL and 18 mL, 48 mL and 12 mL, 54 mL and 6 mL, respectively. The filter cake was then washed and pulped with 60 mL of a mixed solution of tBuOH and 30 mL of deionized water at 50°C and 300 rpm for 30 minutes. The filter cake was washed with tBuOH and then centrifuged at 5000 rpm for 5 minutes to separate the filter cake. The filter cake was then dried in a 50°C vacuum drying oven to constant weight, then ground and sieved through a 100-mesh iron sieve, and finally vacuum dried at 50°C for 48 hours and protected with high-purity argon for use.
[0058] Example 1
[0059] (1) Preparation of CO2-based elastomers
[0060] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 8.4 mg), cocatalyst (PPNCl, 6.0 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 2.5 mg) and epoxy monomer (allyl glycidyl ether, 0.5 mL; 1,2-epoxyhexane, 4.5 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (60 ° C, 4 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 6 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0061] A small portion of the crude product was taken and measured by 1H NMR spectroscopy. The conversion rates of allyl glycidyl ether and 1,2-epoxyhexane monomers were 85% and 82%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content (carbonate content = carbonate segment in copolymer / (carbonate segment + ether segment)) as 83%, ether segment content as 17%, and number average molecular weight as 113 kg / mol.
[0062] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0063] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0064] Example 2
[0065] (1) Preparation of CO2-based elastomers
[0066] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 11.2 mg), cocatalyst (PPNCl, 8.0 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 1.5 mg) and epoxy monomer (allyl glycidyl ether, 0.5 mL; 1,2-epoxyhexane, 4.5 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (65 ° C, 5 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 6 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0067] A small portion of the crude product was taken and measured by 1H NMR spectroscopy, and the conversion rates of allyl glycidyl ether and 1,2-epoxyhexane monomers were 88% and 83%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 87%, ether segment content 13%, number average molecular weight 106kg / mol).
[0068] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0069] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0070] Example 3
[0071] (1) Preparation of CO2-based elastomers
[0072] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 11.2 mg), cocatalyst (PPNCl, 4.0 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 1.5 mg) and epoxy monomer (allyl glycidyl ether, 1.6 mL; 1,2-epoxyhexane, 3.4 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (75 ° C, 4 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 6 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0073] A small portion of the crude product was taken and measured by 1H NMR spectroscopy to determine that the conversion rates of allyl glycidyl ether and 1,2-epoxyhexane monomers were 99% and 99%, respectively. The remaining product was dissolved in dichloromethane and then precipitated by adding excess methanol to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 81%, ether segment content 19%, number average molecular weight 66kg / mol).
[0074] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0075] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0076] Example 4
[0077] (1) Preparation of CO2-based elastomers
[0078] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 8.4 mg), cocatalyst (PPNCl, 6.0 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 3.5 mg) and epoxy monomer (allyl glycidyl ether, 0.25 mL; 1,2-epoxyhexane, 4.75 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (55 ° C, 4 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 6 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0079] A small portion of the crude product was taken and measured by 1H NMR spectroscopy, and the conversion rates of allyl glycidyl ether and 1,2-epoxyhexane monomers were 82% and 79%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 86%, ether segment content 14%, number average molecular weight 102kg / mol).
[0080] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0081] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0082] Example 5
[0083] (1) Preparation of CO2-based elastomers
[0084] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 8.4 mg), cocatalyst (PPNCl, 6.0 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 2.5 mg) and epoxy monomer (allyl glycidyl ether, 0.34 mL; 1,2-butylene oxide, 4.66 mL) were added to a pre-dried autoclave. The reactor was then heated and charged (60 ° C, 4 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 6 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0085] A small portion of the crude product was taken and measured by 1H NMR spectroscopy, and the conversion rates of allyl glycidyl ether and 1,2-butylene oxide monomers were 94% and 89%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 87%, ether segment content 13%, number average molecular weight 89kg / mol).
[0086] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0087] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0088] Example 6
[0089] (1) Preparation of CO2-based elastomers
[0090] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 8.4 mg), cocatalyst (PPNCl, 6.0 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 2.5 mg) and epoxy monomer (allyl glycidyl ether, 0.2 mL; 1,2-epoxyoctane, 4.8 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (60 ° C, 3 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 6 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0091] A small portion of the crude product was taken and measured by 1H NMR spectroscopy, and the conversion rates of allyl glycidyl ether and 1,2-epoxyoctane monomers were 86% and 81%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 83%, ether segment content 17%, number average molecular weight 96kg / mol).
[0092] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0093] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0094] Example 7
[0095] (1) Preparation of CO2-based elastomers
[0096] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 10.0 mg), cocatalyst (PPNCl, 7.2 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 2.5 mg) and epoxy monomer (allyl glycidyl ether, 0.66 mL; 1,2-butylene oxide, 4.34 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (65 ° C, 5 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 6 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0097] A small portion of the crude product was taken and measured by 1H NMR spectroscopy, and the conversion rates of allyl glycidyl ether and 1,2-butylene oxide monomers were 84% and 80%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 85%, ether segment content 15%, number average molecular weight 78kg / mol).
[0098] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0099] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0100] Example 8
[0101] (1) Preparation of CO2-based elastomers
[0102] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 10.0 mg), cocatalyst (PPNCl, 7.2 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 1.5 mg) and epoxy monomer (allyl glycidyl ether, 0.4 mL; 1,2-epoxyoctane, 4.6 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (70 ° C, 5 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 5 h of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0103] A small portion of the crude product was taken and measured by 1H NMR spectroscopy, and the conversion rates of allyl glycidyl ether and 1,2-epoxyoctane monomers were 87% and 83%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 75%, ether segment content 25%, number average molecular weight 74kg / mol).
[0104] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0105] The carbon dioxide-based elastomer (3 g) and dicumyl peroxide (DCP) (0.0015 g) were dissolved in tetrahydrofuran (10 mL) and stirred at room temperature to completely dissolve. The solvent was then evaporated at room temperature. The resulting mixture was cross-linked at 160° C. and 15 MPa for 0.5 hours to obtain a cross-linked carbon dioxide-based elastomer. The sample was allowed to stand for 12 hours before being subjected to a tensile test.
[0106] Example 9
[0107] (1) Preparation of CO2-based elastomers
[0108] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 10.5 mg), cocatalyst (PPNCl, 7.5 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 3.1 mg) and epoxy monomer (allyl glycidyl ether, 2.3 mL; 1,2-epoxyhexane, 22.7 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (70 ° C, 4 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 12 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0109] A small portion of the crude product was taken and measured by 1H NMR spectroscopy to determine that the conversion rates of allyl glycidyl ether and 1,2-epoxyhexane monomers were 85% and 80%, respectively. The remaining product was dissolved in dichloromethane and then precipitated by adding excess methanol to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 83%, ether segment content 17%, number average molecular weight 127kg / mol).
[0110] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0111] The carbon dioxide-based elastomer (50 g) and dicumyl peroxide (DCP) (0.025 g) were mixed in an internal mixer at room temperature for 10 minutes to make them uniformly dispersed. Subsequently, they were crosslinked at 160° C. and 15 MPa for 0.5 hours to obtain a crosslinked carbon dioxide-based elastomer. The crosslinked elastomer was left to stand for 12 hours and then subjected to a tensile test.
[0112] Example 10
[0113] (1) Preparation of CO2-based elastomers
[0114] In a glove box with argon atmosphere, homogeneous catalyst (Al porphyrin, 10.5 mg), cocatalyst (PPNCl, 7.5 mg) and heterogeneous catalyst (Zn-Co double metal cyanide, 3.1 mg) and epoxy monomer (allyl glycidyl ether, 1.3 mL; 1,2-epoxyhexane, 23.7 mL) were added to a pre-dried autoclave. The reactor was then heated and pressurized (60 ° C, 5 MPa CO2) to reach the required temperature and carbon dioxide pressure. After 12 hours of reaction, the reactor was placed in an ice water bath to cool and slowly release the CO2 pressure.
[0115] A small portion of the crude product was taken and measured by 1H NMR spectroscopy, and the conversion rates of allyl glycidyl ether and 1,2-epoxyhexane monomers were 81% and 78%, respectively. The remaining product was dissolved in dichloromethane, and then an excess of methanol was added for precipitation to remove unreacted monomers and small molecular by-products. The precipitated polymer was collected and vacuum dried at 40°C for 48 hours to obtain a carbon dioxide-based elastomer. A small amount of purified polymer was measured by 1H NMR and gel permeation chromatography (GPC) to determine its carbonate content and molecular weight (carbonate segment content 88%, ether segment content 12%, number average molecular weight 141kg / mol).
[0116] (2) Preparation of cross-linked carbon dioxide-based elastomers
[0117] The carbon dioxide-based elastomer (50 g) and dicumyl peroxide (DCP) (0.025 g) were mixed in an internal mixer at room temperature for 10 minutes to make them uniformly dispersed. Subsequently, they were crosslinked at 160° C. and 15 MPa for 0.5 hours to obtain a crosslinked carbon dioxide-based elastomer. The crosslinked elastomer was left to stand for 12 hours and then subjected to a tensile test.
[0118] Comparative Example 1: Preparation of CO2-based elastomer using only homogeneous catalyst
[0119] The preparation process in Example 1 was adopted, except that only Al porphyrin was used as the catalyst.
[0120] The test results show that the reaction has almost no induction period, the conversion rate of epoxy monomer is 30%, the content of cyclic carbonate in the product is 5%, the content of carbonate segments in the purified polymer is 100%, there is no ether segment, the number average molecular weight is 20kg / mol, the molecular weight distribution index (PDI) is 1.24, and the glass transition temperature is -6°C. The tensile strength of the prepared cross-linked carbon dioxide-based elastomer is only 0.5MPa, and the elongation at break is 197%. Compared with Example 1, the catalytic efficiency, product molecular weight and mechanical properties are significantly reduced.
[0121] Comparative Example 2: Preparation of CO2-based elastomer using only heterogeneous catalyst
[0122] The preparation process in Example 1 was adopted, except that only Zn-Co double metal cyanide was used as the catalyst.
[0123] The test results show that the reaction induction period is >2h, the conversion rate of epoxy monomer is 99%, the cyclic carbonate content in the product is 3%, the carbonate segment content in the polymer obtained after purification is 65%, the ether segment content is 35%, the number average molecular weight is 45kg / mol, the molecular weight distribution index (PDI) is 2.65, and the glass transition temperature is -17°C. The tensile strength of the prepared cross-linked carbon dioxide-based elastomer is only 0.5MPa, and the elongation at break is 467%. Compared with Example 1, the carbonate segment content, product molecular weight and mechanical properties are significantly reduced.
[0124] Table 1 shows the performance test results of the carbon dioxide-based elastomer and the cross-linked carbon dioxide-based elastomer prepared in Examples 1 to 10 and Comparative Examples 1 to 2.
[0125] Table 1
[0126]
[0127] It can be seen from the results in Table 1 that compared with Comparative Examples 1 to 2, the carbon dioxide-based elastomers prepared in Examples 1 to 10 have higher number average molecular weights, and the glass transition temperature (T g ) is +6~-20℃, and has excellent mechanical properties. It can be seen from the comparison of the embodiments and the comparative examples that the present invention significantly reduces the induction period of the reaction through the synergistic effect of the homogeneous catalyst and the heterogeneous catalyst, improves the reaction efficiency, and at the same time improves the molecular weight and mechanical properties of the carbon dioxide-based elastomer. This technology solves the problems of insufficient catalytic activity, unstable reaction, low product molecular weight and poor mechanical properties in the preparation of existing carbon dioxide-based elastomers. Due to its superior performance, the present invention has broad application prospects in the field of preparation of carbon dioxide-based elastomers.
Claims
1. A high molecular weight carbon dioxide based elastomer, obtained by polymerization reaction of components including carbon dioxide and epoxy compounds under the action of a composite catalyst, wherein the composite catalyst comprises a homogeneous catalyst, a heterogeneous catalyst and a co-catalyst.
2. The high molecular weight carbon dioxide-based elastomer according to claim 1, characterized in that The epoxy compound comprises a saturated epoxy compound and an unsaturated epoxy compound; preferably, the saturated epoxy compound is selected from at least one of C3-12 saturated alkyl epoxy compounds, and / or, the unsaturated epoxy compound is selected from at least one of unsaturated glycidyl ether compounds; more preferably, the saturated epoxy compound is selected from at least one of butylene oxide, hexylene oxide, and octane oxide, and / or, the unsaturated epoxy compound is selected from at least one of allyl glycidyl ether and glycidyl methacrylate, and / or, the molar ratio of the saturated epoxy compound to the unsaturated epoxy compound is 1:(0.01-0.5), preferably 1:(0.05-0.3); and / or, The homogeneous catalyst is aluminum porphyrin; and / or, The heterogeneous catalyst is selected from a bimetallic catalyst, preferably a Zn-Co bimetallic cyanide; and / or, The co-catalyst is bis-(triphenylphosphorane)ammonium chloride; and / or, The mass ratio of the homogeneous catalyst, the heterogeneous catalyst and the co-catalyst is 1:(0.05-0.7):(0.2-1.5), preferably 1:(0.1-0.5):(0.3-0.9).
3. A method for preparing the high molecular weight carbon dioxide-based elastomer according to any one of claims 1 to 2, comprising heating and polymerizing the components including the carbon dioxide, epoxy compound, and composite catalyst, and then performing post-treatment to obtain the high molecular weight carbon dioxide-based elastomer.
4. The preparation method according to claim 3, characterized in that: In the composite catalyst, the amount of the heterogeneous catalyst is 0.002-0.12wt% of the total amount of the epoxy compound, preferably 0.008-0.1wt%; and / or, the amount of the homogeneous catalyst is 0.005-0.35wt% of the total amount of the epoxy compound, preferably 0.01-0.28wt%; and / or, the amount of the co-catalyst is 0.005-0.25wt% of the total amount of the epoxy compound, preferably 0.01-0.20wt%; and / or, The polymerization reaction temperature is 50 to 80° C., preferably 55 to 70° C.; and / or, The polymerization reaction pressure is 2-6 MPa, preferably 3-5 MPa; and / or, The polymerization reaction time is 1 to 24 hours, preferably 4 to 16 hours.
5. The preparation method according to claim 3, characterized in that: The post-treatment includes the steps of dissolving, precipitation and drying; preferably, The dissolving solvent used in the dissolving is selected from at least one polar solvent, preferably at least one of dichloromethane and tetrahydrofuran; and / or, The precipitation solvent used in the precipitation is selected from at least one of alcohols, preferably at least one of methanol and ethanol; and / or, The drying temperature is 25-60°C, preferably 30-40°C.
6. A high molecular weight carbon dioxide-based elastomer obtained by the preparation method according to any one of claims 3 to 5; preferably, the number average molecular weight of the high molecular weight carbon dioxide-based elastomer is 50 to 180 kg / mol, preferably 80 to 150 kg / mol.
7. A cross-linked carbon dioxide-based elastomer prepared from a high molecular weight carbon dioxide-based elastomer, wherein the high molecular weight carbon dioxide-based elastomer is the high molecular weight carbon dioxide-based elastomer according to any one of claims 1 to 2 or the high molecular weight carbon dioxide-based elastomer according to claim 6.
8. A method for preparing the cross-linked carbon dioxide-based elastomer according to claim 7, comprising the step of subjecting the high molecular weight carbon dioxide-based elastomer to an initiation reaction to prepare the cross-linked carbon dioxide-based elastomer.
9. The method for preparing a cross-linked carbon dioxide-based elastomer according to claim 8, characterized in that: The specific steps include: The cross-linked carbon dioxide-based elastomer is obtained by mixing the high molecular weight carbon dioxide-based elastomer and the initiator and then heating them for cross-linking reaction; wherein the mixing is optionally carried out in a solvent.
10. The preparation method according to claim 9, characterized in that: The initiator is selected from at least one of peroxide initiators, preferably at least one of dicumyl peroxide, di-tert-butyl peroxide, and 2,5-dimethyl-2,5-di-tert-butylhexane peroxide; and / or, The solvent is selected from at least one of tetrahydrofuran, dichloromethane and toluene; and / or, The amount of the initiator is 0.03-0.20wt% of the amount of the high molecular weight carbon dioxide based elastomer, preferably 0.05-0.15wt%; and / or, The cross-linking reaction temperature is 120-210° C., preferably 150-180° C.; and / or, The pressure of the cross-linking reaction is 10-20 MPa, preferably 13-17 MPa.
Citation Information
Patent Citations
Preparation method of cyclic carbonate
CN104327036A
Preparation method of polycarbonate
CN104448283A
Composite catalyst for ternary copolymerization of carbon dioxide, epoxy propane and lactide and preparation method thereof
CN106957415A
Cited By
Synthetic method and application of elastomer based on C1 monomer
CN121181873A